STUDY OF PREPARATION METHOD IN ANTIOXIDANTS ANALYSIS FROM KELOR SEEDS (Moringa oleifera L.) TOFU COAGULATION - Selly Harnesa Putri; Farah Nuranjani; Irfan Ardiansah (Universitas Padjadjaran, 2017)
Currently, Indonesia is exporter of the moringa seed. Moringa seed is a plant which is contain a vegetable oil with many benefits, especially for health. In addition to the utilization of moringa seeds used as vegetable oils, the seeds of this moringa as a natural coagulant, supported by its antioxidant is suitable combined in its use as a natural coagulant on tofu. The analytical method used in the antioxidant content testing using DPPH method is an easy, fast and sensitive method using DPPH free radical (1,1-diphenyl-2-picrilhidrazil). In antioxidant analysis required materials of extract, which high yield and purity consisting of extraction method of multilevel maceration extraction with 3 solvents (n-hexane, 70% of acetone and 96% of ethanol) 1: 3 solvent and solvent ratio and Ultrasonic Assisted Extraction (UAE). The result of the research showed that the extraction process using multilevel maceration extraction with high yield and purity. Determination of extract concentration for IC50 calculation measured by using a spectrophotometer so that the percentage of inhibition is 722,01 which concentration needed to 50 % can inhibit free radical in antioxidants analysis. The impact of research results is utilized optimally on extract moringa seeds with many benefits especially for health.